Heritage Tourism in Bali: A Study of Public Administration in the Besakih Temple Area - Alvin Andrew Dias; Nyoman Diah Utari Dewi (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Heritage tourism is a strategic sector in Bali’s regional development; however, its management in sacred areas such as Pura Besakih presents complex governance challenges. The urgency of this study lies in the dual function of Pura Besakih as a religious center and a cultural tourism destination, which requires public policies that are sensitive to cultural and spiritual values. This study aims to analyze the governance of heritage tourism at Pura Besakih from a public administration perspective, focusing on the role of government, institutional coordination, and community participation. The research draws on theories of public policy, public governance, and sacred public space. A qualitative approach with a case study design was employed, utilizing in-depth interviews, field observation, and document analysis. The findings indicate that heritage tourism management at Pura Besakih remains largely administrative, with fragmented institutional coordination and limited community involvement in decision-making processes. These results highlight the need for a more collaborative and sustainable governance model to preserve the sacredness and long-term sustainability of the site. Keywords: Heritage Tourism, Public Governance, Pura Besakih.